Inhibitory of activity -glucosidase from ethyl acetate and flavanal compound of the stem-bark of Calophyllum mcrophyllum Scheff - . Frengki; Jamilah Abbas; Surya Wati (Syiah Kuala University, 2013)
Most of Calophyllum genus have been researched and proven as medicinal plants. Calophyllum macrophyllum Scheff is an Indonesia original plant growing on Sumatera and we found in Kerinci mount. One flavanal has been isolated from ethyl acetate fraction from the stem-bark of Calophyllum macrophyllumScheff. The compound is 5,7,2’,5’- tetrahedrons flavan-3-ol, brown crystal with melting point 300oC. The compound was extracted using maceration technique, then fractionated using chromatography and purified by crystallization using two solvents. Molecule structure was determined using physical data and spectroscopy methods including UV, IR and 1H and 13C-NMR. Ethyl acetate fraction and isolate were assayed for inhibitory activity on -glycosidase enzyme. The potential inhibition effect is got each other with IC50 26,198 =g/ml and 12,19 =g/ml.